참조물을 활용한 역동적평가의 교수과정이 유아의 측정능력에 미치는 영향 - 고은미(Eun Mi Ko); 정명숙(Myung Sook Jung); 황해익(Hae Ik Hwang) (Korean Journal of child studies, 2008)
This study investigated the effects of a teaching process using dynamic assessment for a unit on young children's measurement ability. Subjects were 45 5-year-old children in a kindergarten in Busan. The instrument was the Dynamic Assessment Tools for Young Children's Measurement Ability (Hwang & Ko, 2(07). Assessment consisted of four steps: pre-test, learning, transfer, post-test. Results were that at post-test, there were significant differences in scores of measurement ability between the dynamic assessment and control groups. In the dynamic assessment group there was significant improvement in length, width and weight between pre- and post-tests and there were significant shifts of measurement strategies and measurement errors between the pre- and post-tests.